A fully defined artificial diet for Myzus persicae – the detailed technical manual. Issue 6 (8th June 2020) - van Emden, Helmut F.; Wild, Elizabeth A.
Abstract: We have been able to maintain a continuous culture of Myzus persicae (Sulzer) (Hemiptera: Aphididae) on a fully defined artificial diet at Reading, UK, for over 30 years, without any return to plants. Following multiple requests from aphid researchers, here we provide the details of our culturing method. Detailed instructions are given for rearing M. persicae on the diet. An improved recipe is included as well as the construction and changing of diet sachets. Abstract : We have been able to maintain a continuous culture of Myzus persicae (Hemiptera: Aphididae) on a fully defined artificial diet at Reading, UK, for over 30 years, without any return to plants. Following multiple requests from aphid researchers, here we provide the details of our culturing method. Detailed instructions are given for rearing M. persicae on the diet. An improved recipe is included as well as the construction and changing of diet sachets.